POTENTIAL OF BIG DATA FOR PRO-ACTIVE PARTICIPATORY LAND USE PLANNING - Walter Timo de Vries (Geoplanning: Journal of Geomatics and Planning, 2018)
The presence of (spatial) big data presumes that citizens can more actively collect and analyse data for their own land use goals. This article evaluates that claim. Given that land use planning heavily depends on participation and citizens’ own contributions the core question is whether and how (spatial) big data can enhance and/or complement current land use planning endeavours. The article starts by defining and conceptualising the various phases and objectives of land use planning. This is needed to verify where citizen participation can play a crucial role and where bottom-up influence can actually emerge.  The article is fundamentally explorative. It relies on evaluating existing websites and documentation which conceptualise (spatial) big data and smart application, with a particular emphasis on ‘smart people’. A number of specific cases are explored in order to verify how and in which type of land use planning activity citizens are actively.  The evaluation indicates that many the smart applications making use of big data are still largely driven by conventional hierarchical governance structures. The choice of data and associated analytics are still largely confined and the opportunities whereby the designs of the new and alternative land use options by citizens are accepted or adopted is still limited. The take-home message is that adoption of big data for the purpose of empowering citizens is still limited. There probably needs to be more exemplary projects and various forms of capacity development and exploratory pilots before the full potential of (spatial) big data can be employed for bottom-up land use planning.